Synthesis, Microstructure, Optical Properties, and Sensitive Amoxicillin Detection of Carbon Dots - Lubis, Yuni Aldriani; Gea, Saharman; Lubis, Muhammad Frassetia; Pai, Woei Wu Larry; Marpongahtun, Marpongahtun (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
The detection of amoxicillin has been successfully carried out using C-dot fluorescence probes made from d-glucose and urea. The fluorescence probe has an intense bright blue emission under UV light at 395 nm and and depends on the excitation and depends on the excitation. Raman studies successfully showed a D peak at 1381 cm-1 and a G peak at 1586 cm-1 associated with graphitic and amorphous structures. The absorption peaks in UV-vis spectroscopy confirm transitions at 275 nm (π → π*) and 322 nm (n → π*) with the presence of conjugated C=C and carbonyl (C=O) functional groups. The results of the fluorescence test show a bright blue color, with its intensity measured at an excitation of 365 nm. This can be attributed to nitrogen incorporation on the surface of the C-dots derived from urea, resulting in a quantum yield of 54%. This fluorescence probe is highly sensitive in detecting amoxicillin, as evidenced by the successful detection of AMX at concentrations of 10–30 μM and a resulting LOD of 5.75443×10−7 nM. The microstructure shows a uniform size of C-dot nanoparticles, and C-dot modeling was created. C-dot probes have an LOD of 5.75443×10−7 nM, indicating high sensitivity in detecting AMX.